Fallopian tube carcinoma: Energy lost in diagnosing without the total benefit of chemotherapy - Pradhan, Neelam; Ghimire, Sita; Bist, Kesang D; Manandhar, Reeta (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> A post menopausal lady presented with vague symptoms of swelling in lower abdomen giving an impression of left adnexal mass clinically, with detection of similar finding on USG and CT scan, and an additional feature suggestive of liver metastases. On laparotomy this looked like a fallopian tube carcinoma and it was confirmed histologically, which showed infiltration of both the ovaries, left broad ligament, and cervix. FNAC of lymph node depicted metastatic adenocarcinoma, although the tumour markers and Pap test were negative. Patient's refusal to undergo chemotherapy turned down all the efforts made in making the diagnosis of this advanced malignancy. Key words: Adnexal mass, fallopian tube carcinoma, tumour markers doi:10.3126/njog.v2i1.1481 N. J. Obstet. Gynaecol Vol. 2, No. 1, p. 63 - 66 May -June 2007